Green Technology Usage Behaviour in Vocational Education: The Mediating Roles of Perceived Long-Term Benefits - Parinsi, Mario Tulenan; Ratumbuisang, Yosua Fitsgerald; Ratumbuisang, Keith Francis; Farid Mutohhari (Universitas Pendidikan Ganesha, 2024)
The importance of green technology to be applied by vocational education (VE) has not yet been realized in optimal behavior. The strong assumption is that they do not find it instantly beneficial, even though the operational competencies and cultural drivers still need to be understood. This research aims to measure the significance of the influence of green technology competence (GTC), socio-cultural norms (SCN), and perceived long-term benefits (PB) on green technology use behavior (UB). In addition, the mediating role of PB is also tested in bridging the indirect influence of GTC and SCN on UB. The expost-facto study was conducted in VEs with Adiwiyata status with a total involvement of 647 participants who joined as teachers and students. Data collection used a closed questionnaire with four Likert scales that had been tested for validity and reliability. Structural Equation Modeling was used to analyze the data through path analysis and bootstrap methods. This study proved the importance of PB as a determinant of UB in VE teachers and students. It also provides essential insights into how GTC and SCN play an essential role in developing PB and determining UB. These results have important implications for VEs in improving their competencies and socio-cultural foundations to promote the sustainable use of green technologies. VE can synergize with various stakeholders and socio-cultural communities to support the strengthening of social capital and technical and financial assistance. In addition, the adaptive power of VE to analyze the need for green technology integration must also be pursued.